(untitled) (Global Journal of Human-Social Science, 2024)
This article aims to analyze the un necessity of judicializing the supply of the drug Tacrolimus to patients with lupus who have the constitutional right to full health like any citizen Medical studies indicate the use of Tacrolimus in cases where conventional treatments are no longer effective especially when lupus causes kidney impairment Despite its proven effectiveness and the drug s registration with the National Health Surveillance Agency ANVISA Tacrolimus is not standardized by the Unified Health System SUS for the treatment of the disease posing an obstacle to access This scenario forces patients to go to court to obtain the medication which can delay the start of treatment worsening the clinical condition and leading in some cases to the loss of kidney function The 1988 Federal Constitution guarantees the right to life as the primary foundation for the exercise of all other rights Therefore it is argued that the supply of Tacrolimus should be guaranteed immediately by the State eliminating the need for legal action especially for patients with kidney complications associated with lupus thus ensuring the right to life to its fullest